Phenanthrenes from Juncus articulatus with Antibacterial and Biofilm Formation Inhibitory Activity - Barta, Anita (2024)
Continuing our search for bioactive compounds in species from the Juncaceae family, Juncus articulatus was investigated. Ten previously undescribed phenanthrenes articu-lins A−J (1−10) and ten known compounds juncuenin B, dehydrojuncuenin B, juncatrin B, ensifolins E, F, H, I, K, juncuenin D, and luzulin A (11−20) along with other compounds, have been isolated and identified. The isolated compounds were evaluated for antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, methicillin-susceptible Staphylococcus aureus (MSSA), and methicillin-resistant Staphylococcus aureus (MRSA). Compounds 12 and 14 exhibited the most potent activity against planktonic and sessile MSSA and MRSA with minimum inhibitory concentration (MIC) values of 15.1 μM (12 for both bacterial strains) and 15.3 μM (14 for both bacterial strains). Compounds 15, 17, and 18 also exhibited activity against both strains, although to a lower extent, with MIC values ranging from 30.0 to 56.8 μM. The inhibition of biofilm formation of these compounds was observed at 15.1−114.3 μM. This study elucidates the phenanthrene composition of J. articulatus and the antibacterial effect of these compounds